DIFFUSION PROCESSES AND SOME METHODS OF THEIR CONSTRUCTION AND APPLICATIONS - Осипчук, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Work is devoted consideration of diffusion processes of both Markov processes which own some properties and decisions of stochastic differential equations. It enables to design the trajectories of such processes. Possibility of the use of diffusion processes in the tasks of design motion of shallow par- ticles in a mobile environment is applied for determination of distribution of smoke in mid air.